As práticas profissionais de modificações corporais: entre a biossegurança e as técnicas de si - França, Letícia Souto Ribeiro de (2008)
The relation of the human being and his body is crossed by practices of cultural manipulation and temporarily situated. In this work we explore the ways in which the body is being the target of interventions, bringing examples of traditional cultures, its techniques and functions, and we present a discussion about the body modification practices in the contemporary occidental society. Starting with the foucaultian reflection that there is a political technology of the body, we try to keep up with the techniques of the self activated by the body modification professionals and the ways these practices forge its frontiers with others political technologies. For such, we made individual interviews with three body modification professionals, because we believed that they occupy an strategic place in their field: they are not only in relation with the ones who request their work, but also with agencies that socially have any social control mandate over the management of these practices. The way found was to get in touch with The Tattoo and Body Piercing Company Union of the State of São Paulo (SETAP-SP). Found in 2005, the SETAP-SP regularizes the practice of tattoo and body piercing in the state of São Paulo. The constructionist perspective offered us a methodological help on the research allowing a non realistic posture before our object, making possible to recognize the participants speech as knowledge, set in the level of any other discursive production. We proposed, so, dialogues among the practical knowledge of the participants with theoric reflection about self care, biopolitic and biosecurity. According to the analyses, we noticed that the biosecurity practices mentioned by the three interviewed professionals, show us the insertion process of this concern, in the last decades, in the field of body modifications in Brazil. However, if the body modifications are doing interface with the biosecurity optic, they do not stop having frontiers or important interfaces with the health subjetc, but, less in a normative perspective (in the sense of biopolitic) and more as a potency to differ. In other words, less as a norm and more as normativity. Therefore we also conclude that the professional practice of body modification can have distinctive connotations, in this case, close to the clinical practices and the techniques of the self